Digital Access to LRC services and resources during COVID-19 Pandemic: Prince Mohammad Bin Fahd University LRC Experience - Mohamed A. Abdulla (15387420) (2023)
This paper was given by Mohamed A. Abdulla and Elvira A. Zingapan,  Prince Mohammad Bin Fahd University  This study aims to discuss digital access to the Learning Resources Center services and resources during the COVID-19 pandemic.The PMU LRC’s response on the pandemic situation during the periods of closure concerning resources and services is discussed and analyzed. The LRC implements new virtual services and expands the electronic resources to ensure that the PMU community is able to access the resources and information that they needed. The LRC makes efforts to gain access to their digital and physical collections as well as to provide their services remotely, with the transformation of teaching from traditional style to distance learning.There are several virtual initiatives that LRC has taken to promote digital access to the library resources and to make LRC services more efficient while challenging to deliver access to information with library closure. The researchers also examine the changes that PMU library has made to library services throughout the year 2020.